Water Quality Parameters of Rupa Lake in Pokhara,Nepal - Subedi, Thaneshwar (Kalika Journal of Multidisciplinary Studies, 2023)
In this study, physical and biochemical water quality parameters are analyzed from five selected stations in Rupa Lake Pokhara, Nepal using standard procedures. Analyzed parameters are: temperature, turbidity, total solids (TS), electrical conductivity (EC), pH, total alkalinity (TA), total hardness (TH), chloride content, sulphate and dissolved oxygen (DO). Based on the observed water quality parameters, the quality of Rupa Lake water is discussed and compared with WHO standard values for drinking water. Recorded laboratory results shows that water of Rupa Lake is useful for agricultural, industrial, aquatic life, and fishery purposes.